Sequence { a n } satisfies the following conditions: a 3 = 6 3 , a n + 1 = 4 a n + 3 . Find the minimum positive integer n that satisfies a n + 1 > a n + 3 0 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Or you can simplify the inequality as a n > 9 9 and then use the given recurrence to list out a n values ∀ n ∈ N where the sequence is defined and give the answer by matching the a n values with the inequality.
a n + 1 = 4 a n + 3
I will prove with induction that a n = 4 n − 1 . For n = 3 → a 3 = 4 3 − 1 = 6 3 . Suppose that for any integer k the equation is demonstrated, we have to prove a k + 1 = 4 k + 1 − 1 .
From hypothesis: a k + 1 = 4 a k + 3
From inductive hypothesis a k + 1 = 4 ( 4 k − 1 ) + 3 → a k + 1 = 4 k + 1 − 1 as we want.
So, a n + 1 > a n + 3 0 0 → 4 n + 1 − 1 > 4 n − 1 + 3 0 0 → 4 n ( 4 − 1 ) > 3 0 0 → 4 n > 1 0 0 Hence n = 4 .
Given conditions an+1 > an + 300 and an+1= 4an + 3 So 4an + 3 > an + 300 => an > 99 Since, a3 is given as 63, So, a4 will be 4*63 + 3 That definitely seems greater than 99.
We can find the explicit formula for a n which is 4 n − 1
n = 4 is obviously the answer
Problem Loading...
Note Loading...
Set Loading...
a4 = a3 +3 = (63*4) + 3 = 255
which doesn't satisfy the condition as 255<363 when n=3
a5 = a4 +3 = (255*4) + 3 = 1023
and when n=4 it satisfies the condition..